Innovative Security Solutions for Information Technology and Communications: 8th International Conference, SECITC 2015, Bucharest, Romania, June 11-12, 2015. Revised Selected Papers - Bica, Ion; Naccache, David; Simion, Emil (LNCS sublibrary. SL 4, Security and cryptology, 2016)
This book constitutes the thoroughly refereedpost-conference proceedings of the 8th International Conference on Security forInformation Technology and Communications, SECITC 2015, held in Bucharest, Romania,in June 2015.The 17 revised full papers were carefully reviewed andselected from 36 submissions. In addition with 5 invited talks the papers covertopics such as Cryptographic Algorithms and Protocols, Security Technologiesfor IT&C, Information Security Management, Cyber Defense, and DigitalForensics.